Developmental changes in haemocyte morphology in response to Staphylococcus aureus and latex beads in the beetle Tenebrio molitor L. (January 2018) - Urbański, Arkadiusz; Adamski, Zbigniew; Rosiński, Grzegorz
Highlights: Developmental changes in the morphology of T. molitor haemocytes were observed. Haemocytes of larvae and 4-day-old adult males had the highest adhesion abilities. Haemocytes of T. molitor react differently to S. aureus and latex beads. Development-specific response to bacteria and latex beads were reported. Abstract: The evolutionary success of insects is undoubtedly related to a well-functioning immune system. This is especially apparent during insect development by the adaptation of individuals to the changing risk of infection. In addition, current studies show that the insect immune system is characterized by some specificity in response to natural pathogens (for example, bacteria, viruses or fungi) and artificial challengers (for example, latex beads or nylon filaments). However, developmental changes and the specificity of immune system reactions simultaneously have not been analysed. Thus, the aim of the present research was to determine changes in haemocyte morphology in response to attenuated Staphylococcus aureus and latex beads across each developmental stage of the beetle Tenebrio molitor . The results of the present research clearly showed differences in the morphology of T. molitor haemocytes during development. The haemocytes of larvae and 4-day-old adult males were characterized by the highest adhesion ability, which was expressed as the largest average surface area, filopodia length and number of filopodia. In contrast, the haemocytes of pupae and 30-day-old adult males had a significantly lower value for these morphological parameters, which was probably related to metamorphosis (pupae) and immunosenescence (30-day-old adults). The haemocytes of the tested individuals reacted differently to the presence of S. aureus and latex beads. The presence of S. aureus led to a significant decrease in all previously mentioned morphological parameters in larvae and in both groups of adult individuals. In these groups, incubation of haemocytes with latex beads caused only a slight decrease in surface area and filopodia length and number. This morphological response of haemocytes to biotic and artificial challengers might be related to an increase in the migration abilities of haemocytes during infection. However, the differences in haemocyte reactivity towards S. aureus and latex beads might be explained by differences in pathogen recognition. Conversely, increased adhesive abilities of pupal haemocytes were also observed, which might be related to the specificity of metamorphosis and the hormonal titre during this developmental stage.